2020
DOI: 10.1016/j.ecolind.2019.105683
|View full text |Cite
|
Sign up to set email alerts
|

The influence of bioactive mobile telephony radiation at the level of a plant community – Possible mechanisms and indicators of the effects

Abstract: Environmental exposure to radiofrequency electromagnetic fields (RF-EMFs) from mobile telephony has rapidly increased in the last two decades and this trend is expected to continue. The effects of this exposure at plant community level are unknown and difficult to assess in a scientifically appropriate manner. Such an assessment can be scientifically adequate if a studied plant community is completely new and control-impact radiation treatment is used. In this review we aimed to predict ecological effects and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 80 publications
1
6
1
Order By: Relevance
“…Moreover, the observed differences in plant responses such as seed germination rate and selected gene expressions at 1837.50 MHz, 2.75 W/m 2 EM irradiation level with respect to the sham‐exposure power density level of 0.07 W/m 2 , is in fact novel. In most of the earlier cases, plant responses were reported at power density levels either below or at a comparable value near 0.07 W/m 2 [Vian et al, 2006; Roux et al, 2006, 2008b; Beaubois et al, 2007; Sharma et al, 2009; Singh et al, 2012; Pesnya and Romanovsky, 2013; Halgamuge et al 2015; Grémiaux et al, 2016; Waldmann‐Selsam et al, 2016; Stefi et al, 2017; Czerwinski et al, 2020]. Hence, the observations in this study along with reported data in literature altogether indicate dose‐dependent (frequency of irradiation, EM power density level, exposure time, plant age, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the observed differences in plant responses such as seed germination rate and selected gene expressions at 1837.50 MHz, 2.75 W/m 2 EM irradiation level with respect to the sham‐exposure power density level of 0.07 W/m 2 , is in fact novel. In most of the earlier cases, plant responses were reported at power density levels either below or at a comparable value near 0.07 W/m 2 [Vian et al, 2006; Roux et al, 2006, 2008b; Beaubois et al, 2007; Sharma et al, 2009; Singh et al, 2012; Pesnya and Romanovsky, 2013; Halgamuge et al 2015; Grémiaux et al, 2016; Waldmann‐Selsam et al, 2016; Stefi et al, 2017; Czerwinski et al, 2020]. Hence, the observations in this study along with reported data in literature altogether indicate dose‐dependent (frequency of irradiation, EM power density level, exposure time, plant age, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…In addition, immediate molecular responses in Satabdi were also studied following short-duration instantaneous EM irradiation (2 h 30 min) to extend the investigations performed by Roux et al [2006Roux et al [ , 2008b and Vian et al [2006Vian et al [ , 2016. It should be noted that the present investigation was performed at 1837.50 MHz, 2.75 W/m 2 treatment level (comparable with international EM guidelines [Cleveland et al, 1997;ICNIRP, 2020]), and this exposure level was different from EM stimulations reported earlier [Roux et al, 2006[Roux et al, , 2008bVian et al, 2006;Beaubois et al, 2007;Sharma et al, 2009;Singh et al, 2012;Pesnya and Romanovsky, 2013;Halgamuge et al, 2015;Grémiaux et al, 2016;Waldmann-Selsam et al, 2016;Stefi et al, 2017;Czerwinski et al, 2020]. Altogether, this investigation has a direct link with human food habits, farmers, and the agricultural economy of several countries.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…1837.50 MHz, 2.75 mW/m 2 was far below the international EM regulations [Cleveland et al, 1997;ICNIRP, 2020]. Moreover, the same was somewhat different from most of the previously reported EM stimulation levels except recent one in 2021 [Roux et al, 2006[Roux et al, , 2008aVian et al, 2006;Beaubois et al, 2007;Sharma et al, 2009;Singh et al, 2012;Pesnya and Romanovsky, 2013;Halgamuge et al, 2015;Grémiaux et al, 2016;Waldmann-Selsam et al, 2016;Stefi et al, 2017;Czerwinski et al, 2020;Kundu et al, 2021b,c].…”
Section: Introductionmentioning
confidence: 76%
“…; mineralization library refers to debris and nutrients related to research objects Substance parameters, most of which will not change with the change of the research object. Therefore, the parameters involved in the AQUATOX model cover many aspects, with a large number, reaching hundreds of [16][17].…”
Section: Aquatox Modelmentioning
confidence: 99%